Effectiveness of business leadership in the Eurasian context: empirical evidence from Kazakhstan. Issue 6 (1st April 2020) - Mahmood, Monowar; Uddin, Md. Aftab; Ostrovskiy, Alexandr; Orazalin, Nurlan
Abstract : Purpose: Based on the tenets of the conservation of resources (COR) theory, this study investigated the influence of different leadership styles on organizational performance in the context of a Eurasian country (i.e. Kazakhstan). It further examined the moderating role of corporate culture in the leadership-organizational performance relationship. Design/methodology/approach: Using the quantitative survey method, the study collected data from 321 managerial employees working in local and multinational corporations in Kazakhstan. The collected data were analysed using SPSS software, and factor analysis, path analysis and hierarchical regression analysis were conducted to validate the hypotheses. Furthermore, structural equation modelling was developed to assess the moderating effects of the variables. Findings: The findings reveal that among different leadership styles, transformational, transactional and paternal leadership have higher influences on organizational performance. Among different corporate cultures, clan culture appears to have higher moderating effects on the leadership-organizational performance relationship. The moderating role of corporate culture on the leadership influence-organizational performance relationship supports the "resource caravan" effects of the composition model theory. Research implications: Based on the premises of the COR theory, this study suggests developing multiple leadership competencies among managerial employees to be more effective in any given organizational or country context. As a result of the inclusiveness of multiple competencies, the study further suggests the consideration of an "integrated leadership approach" in the Eurasian context. Consistent with the national cultural syndrome, and as preferred by employees, managers could focus on developing a clan or group culture to strengthen their influencing power on employees. Originality/value: The study adopts the COR theory by considering leadership competencies as unique resources of individual managers, which suggests the development of an "integrated leadership approach" for better management development and improved organizational performance. Furthermore, the study contributes by validating the applicability of the "conservation of resources" and the "composition model" theories in leadership studies.